The dawn of succinylation: a posttranslational modification - Alleyn, Matthew (Am J Physiol Cell Physiol, 2018)
Posttranslational modifications affect almost all proteins and are critical to a well-functioning and diverse proteome; however, many modifications remain relatively unknown and unstudied. This paper will give a perspective on the rapidly developing, novel posttranslational modification called succinylation. This modification may be implicated in numerous diseases, such as hepatic, cardiac, and pulmonary diseases. Although the influences of this modification still remain poorly understood, we are confident that further research into succinylation will provide an enhanced understanding of the complex machinery within the mitochondria, as well as the imposing consequences associated with its dysfunction.